2022
DOI: 10.3390/antiox11102081
|View full text |Cite
|
Sign up to set email alerts
|

Carica papaya Reduces Muscle Insulin Resistance via IR/GLUT4 Mediated Signaling Mechanisms in High Fat Diet and Streptozotocin-Induced Type-2 Diabetic Rats

Abstract: In the management of type 2 diabetes, oral antidiabetic drugs have several side effects, which in turn have led the pharmaceutical industry to search for good therapeutic, non-toxic and reliable drugs. Carica papaya (C. papaya) is one of several plants in nature that have been found to possess anti-diabetic properties. Despite studies being focused on the antidiabetic activity of C. papaya, the molecular mechanism against high fat diet induced insulin resistance is yet to be identified. The role of C. papaya w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…4 a). IR and GLUT4 muscle expression was elevated by ethanolic PL extracts in diabetic mice, as demonstrated by Roy et al [ 37 ]. This effect may be due to papaya's phenols and flavonoids [ 30 ].…”
Section: Discussionmentioning
confidence: 71%
“…4 a). IR and GLUT4 muscle expression was elevated by ethanolic PL extracts in diabetic mice, as demonstrated by Roy et al [ 37 ]. This effect may be due to papaya's phenols and flavonoids [ 30 ].…”
Section: Discussionmentioning
confidence: 71%
“…In our earlier research, we found that C. papaya can restore glycemic control by exhibiting insulinemic action in T2DM skeletal muscle by increasing the levels of IR, IRS-1, Akt, and GLUT-4. The potential influence of C. papaya on insulin-signaling molecules in skeletal muscle was shown in a HFD-STZ-induced T2DM model [ 55 , 56 ]. In light of this, we centered on oxidative stress, gluconeogenic-glycolytic enzymes, and the expression of genes in the hepatic tissues of diabetic rats, and assessed the effect of C. papaya on hepatic insulin resistance using in vivo and in silico models.…”
Section: Discussionmentioning
confidence: 99%
“…"Metabolic syndrome" ailments such as diabetes destroy the balance of glucose homeostasis and cause systematic endocrine disorder, but can be corrected by the upregulation of the GLUT4 gene. A study has shown that the ethanolic extract of papaya leaf can reduce muscle insulin resistance by upregulating glut-4 in high-fat-dietand streptozotocin-induced type 2 diabetes in rats [54]. The effects of aqueous guava leaf extract on insulin resistance and glucose transportation were evaluated in an insulinresistant C57BL/6J mice model induced by a high-fructose-high-fat diet [55].…”
Section: Discussionmentioning
confidence: 99%